Hubungan Self Efficacy dengan Hardiness pada Pedagang Kaki Lima di Kota Bukittinggi - Rahma, Puput Nofia; Primanita, Rida Yanna (Lembaga Yasin AlSys, 2025)
Street vendors (pedagang kaki lima, PKL) play a strategic role in the informal sector, contributing significantly to the local economy despite facing numerous challenges such as extreme weather, financial limitations, and unsupportive government policies. Their resilience in confronting these conditions reflects a potential for high psychological hardiness. This study aims to explore the correlation between self-efficacy and hardiness among street vendors in Bukittinggi City. A quantitative correlational approach was employed, involving a sample of 111 vendors selected through purposive sampling. The instruments used included a self-efficacy scale developed based on Bandura's (1997) theory and a hardiness scale grounded in Kobasa's (1979) framework, both of which were tested for validity and reliability. Data analysis was conducted using Pearson Product Moment correlation via SPSS version 21. The results showed a positive and significant relationship between self-efficacy and hardiness (r = 0.624; p < 0.05), indicating that individuals with higher confidence in their abilities tend to possess greater psychological resilience. The study concludes that self-efficacy plays a crucial role in shaping the psychological hardiness of street vendors in coping with everyday stressors and life challenges. These findings have practical implications for developing empowerment-based psychological interventions within the informal sector.